RIAU PROVINCIAL GOVERNMENT POLICY IN THE MANAGEMENT PT RIAU PETROLEOM YEAR 2013-2015 - Iqtisadullah Muttaqin; Auradin Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
PT Riau Petroleum is one of the Regional Owned Enterprises (BUMD) of Riau Province which has the greatest disadvantage compared with another Riau enterprises. Riau Province Government is the majority shareholder in these enterprises. Initiation of the establishment of PT Riau Petroleum comes from Riau Governor at that time. Many things become the background PT Riau Petroleum was formed, including the momentum of regional autonomy and also the circumstances Riau at the time and the desire to cultivate the crops of their own. After trying to establish PT Riau Petroleum, which was funded from the budget of the province of Riau, PT Riau Petroleum have not been able to provide dividends to the Province of Riau since it was founded in 2002.For solving the problem in this research carried out by qualitative descriptive method by collecting data through interviews and searches of documentation ranging from general data that is fundamental. The informant who helped answer the results of this study are the parties directly concerned by PT Riau Petroleum. Starting from the Riau Provincial Government, Board of Commissioners, academics and other parties, and prepare to interpret, analyze, explore and explain more clearly the various factors that related to the research.The results of this study illustrate that the policy of the Government of Riau Province is working to get the right land management Block Siak to be managed by PT Riau Petroleum, which is currently Pertamina as the operator found a bright spot and to save PT Riau Petroleum from being bankrupted, with the help of fund from province Riau which is certainly not closed, in accordance with the recommendations of the Riau Provincial parliament, by no longer providing assistance and budget given by Riau Province's for capital of PT Riau Petroleum by cooperating third parties (investors).Keywords: Policy, PT Riau Petroleum